STUDENT PERCEPTION OF THE QUALITY OF SERVICE IN THE MASTER OF MANAGEMENT STUDY PROGRAM OF UNIVERSITAS TEKNOLOGI YOGYAKARTA - Widyanti, Ratri Nurina (Jurnal Manajemen Bisnis, 2019)
Quality of service is a major supporter in building public trust in the quality of services in the field of education. As users of services in the field of education, student satisfaction needs to be a priority and attention in providing service. This paper aims to analyze student perceptions of service quality and analyze the effect of service quality gaps on the expectations of students of the MM-UTY Program, with a case study in the Master of Management Study Program of the Universitas Teknologi Yogyakarta (Prodi MM-UTY). The concept used as the analysis was service quality, with data collection methods carried out through observation, questionnaires, and interviews. The analytical method used to test the research instrument was factor analysis to test the construct validity and reliability. The results of this study indicate the perception of student satisfaction with the quality of services conducted by the Prodi MM-UTY. Likewise, the average Gap score is positive so that the quality of service at this time is sufficient to meet the expectations and desires of students, which in general need to be maintained. However, partially, there are still some services in Prodi MM-UTY experiencing gaps so that it is necessary to improve the quality of sustainable services.